2021
DOI: 10.1587/transinf.2020edp7245
|View full text |Cite
|
Sign up to set email alerts
|

Online Collaborative Kit-Build Concept Map: Learning Effect and Conversation Analysis in Collaborative Learning of English as a Foreign Language Reading Comprehension

Abstract: Concept map has been widely used as an interactive media to deliver contents in learning. Incorporating concept maps into collaborative learning could promote more interactive and meaningful learning environments. Furthermore, delivering concept maps in a digital form, such as in Kit-Build concept map, could improve learning interaction further. Collaborative learning with Kit-Build concept map has been shown to have positive effects on students' understanding. The way students compose their concept maps while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
2
17
0
1
Order By: Relevance
“…1000 read and write transactions accessing the database were simulated and started. The experiment was carried out in several times and different read and write ratios were set [21]. The time for each transaction to run independently is set to 0.6 s. The time taken to complete the analysis transaction execution is compared at the same time.…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%
“…1000 read and write transactions accessing the database were simulated and started. The experiment was carried out in several times and different read and write ratios were set [21]. The time for each transaction to run independently is set to 0.6 s. The time taken to complete the analysis transaction execution is compared at the same time.…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%
“…The sample in a study is a group of respondents who are contributors to the necessary information. Found that 9 articles involving a sampling size not exceeding 30 respondents in each group after reviewing selected studies (Ghuzayyil, 2019;Ali & Amin, 2019;Bita & Vahideh, 2020;Liu & Yuizono, 2020;Salem & Omran, 2020, Rafidah et al 2021, Pinandito et al 2021, Wafa' & Moath 2021. The sampling size between the selected studies was similar.…”
Section: Sampling Size and Focus Of Selected Studiesmentioning
confidence: 99%
“…The effects of Kit-Build concept maps and common open-end concept maps are compared in the reading element. After making a comparison, it was found that the Kit-Build concept map had a better effect in the collaborative learning of English language comprehension and reading (Pinandito et al, 2021).…”
Section: Reading Abilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Distance English education platforms like ABC360 and Rocky English provides a new learning model, which facilitates the autonomous English learning [11][12][13][14][15][16]. Given a computer or smartphone with Internet access, students can learn English autonomously anytime, anywhere, including applied oral English like English for overseas studies and workplaces [17][18][19][20][21][22][23][24]. With students as the subjects, the autonomous English learning is immune to the interference from any people or things.…”
Section: Introductionmentioning
confidence: 99%